Pengelolaan Media Sosial Instagram @Finansialku_com dalam Membangun Citra Perusahaan - Putri, Della Kurnia (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2024)
This study aims to describe the process of managing Instagram social media in building a corporate image carried out by Finansialku through Instagram @finansialku_com. The researcher describes the social media management process starting from fact finding, planning, implementation, and evaluation. This study uses the four-step public relations concept from Cutlip, Center, and Broom. The paradigm used in this research is constructivism. The approach used is qualitative. The method used in this research is descriptive analysis. Data collection techniques used were in-depth interviews, passive participant observation, and documentation.